How can luxury cosmetic companies leverage on global shoppers: the case study of Kiehl´s since 1851 - Dias, Catarina Fernandes (2017)
The presented case study aims to study the importance of global shoppers for the development of luxury cosmetic brand, Kiehl’s Since 1851, in Portugal. Nowadays, in Portugal, the brand has two major problematics regarding global shoppers: no loyalty and no registration. Having in consideration these two problematics, could Kiehl’s Since 1851 leverage their business on these international consumers? Which markets should the brand prioritize its marketing and communication efforts? A deep qualitative and quantitative analysis concluded that Kiehl’s Since 1851 Portugal should target mainly Chinese and Brazilian international shoppers and should develop tailor made strategies adapted to each market. Marketing, merchandising and educational recommendations were developed, mainly focusing on the brand’s superior and distinctive customer experience. However, and since destination managements organizations (DMO) also play a crucial role in the attraction of these international consumers, Kiehl’s Since 1851 should partner with the different tourism stakeholders to enhance its strength in the attraction of global shoppers. In fact, and despite the fact that Lisbon was considered the 7th European shopping destination, there is still a large margin for improvement and to increase the attractiveness and the competitiveness of the city in this field and therefore recommendations for DMO were also proposed.